Rút gọn biểu thức P với [tex]x \neq 9 ; x\geq 0[/tex]
ĐKXĐ: [tex]x> 0[/tex] và x khác 9
[tex]\left ( \frac{\sqrt{x}}{\sqrt{x}+3} +\frac{x+9}{9-x}\right ):\left ( \frac{3\sqrt{x}+1}{x-3\sqrt{x}}-\frac{1}{\sqrt{x}} \right )[/tex]
[tex]= \left ( \frac{\sqrt{x}.(3-\sqrt{x})+x+9}{(3+\sqrt{x})(3-\sqrt{x})} \right ):\left ( \frac{3\sqrt{x}+1-(\sqrt{x}-3)}{\sqrt{x}(\sqrt{x}-3)} \right )[/tex]
[tex]= \frac{3\sqrt{x}+9}{(3+\sqrt{x})(3-\sqrt{x})}.\frac{\sqrt{x}.(\sqrt{x}-3)}{2\sqrt{x}+4}[/tex]
[tex]= \frac{-3\sqrt{x}}{2\sqrt{x}+4}[/tex]